Release agent composition, hard release paper and release film
By using release agent compositions of specific mass ratios, including alkyd resins, amino resins and organopolysiloxanes, the problems of large peelability changes, deterioration of surface state and insufficient reusability in the prior art are solved, and a release agent composition with high gloss, low depressions and good surface state are achieved.
Patent Information
- Application Number
- CN202380056287.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-08
- Filing Date
- 2023-07-21
- Publication Date
- 2025-03-11
AI Technical Summary
The conventional release agent composition changes greatly when repeatedly used, and the surface state deteriorates, and the reusability is insufficient, making it difficult to meet the requirements of high gloss, few recesses and good surface state in the manufacture of synthetic leather.
The release agent composition with a specific mass ratio, including an alkyd resin having a hardness of 8 to 30 MPa, an amino resin, and an organopolysiloxane having a functional group that can be chemically bonded to the alkyd resin and the amino resin, is used to inhibit the migration of the silicone resin by chemical bonding to form a stable release layer.
A release agent composition with good peelability and reusability is achieved, ensuring excellent glossiness of the coated film, good surface condition, and reducing depression.
Smart Images

Figure BDA0005256990710000081 
Figure BDA0005256990710000091 
Figure BDA0005256990710000131
Abstract
Description
Technical Field
[0001] The present invention relates to a release agent composition, and a hard release paper and a release film. Background Art
[0002] Conventionally, a release agent is applied to the surface of a sheet-like substrate such as paper or plastic to form a cured film, thereby imparting release properties to adhesive or pressure-sensitive adhesive substances.
[0003] The use of release paper and release film covers a wide range of applications, including use for pressure-sensitive adhesive materials such as labels, stickers, and tapes, and use in the molding process of non-pressure-sensitive adhesive materials such as ceramic layers and urethane resins. Different performances are required depending on the application.
[0004] As an example of a process paper used in the molding process of a non-pressure-sensitive adhesive substance, process paper for synthetic leather production can be cited. In the process of synthetic leather production, a release agent is cured on a substrate to form process paper, a urethane resin, a vinyl chloride resin, a polyamide resin, a polyamino acid resin, etc. is coated on the process paper, and the process paper is dried. An adhesive layer is formed on the dried resin, a base cloth is attached, and the resin is peeled off from the process paper to produce synthetic leather.
[0005] Synthetic leathers are classified into matte (dull) type and enamel (high gloss) type. In the production of enamel type synthetic leathers, the surface state of the release agent film is reflected on the synthetic leather. Therefore, a release agent film with high gloss, few dents, and good surface state is required. In addition, in order to improve the productivity of synthetic leathers, process paper is generally used multiple times. Therefore, it is desired that the change in release properties (release properties) is small when used repeatedly.
[0006] For example, Patent Document 1 discloses a release agent composition for process release paper, which is composed of an alkyd resin, an amino resin, and a silicone resin containing a functional group reactive with the alkyd resin and the amino resin, wherein the amino resin contains a methylated melamine resin containing one or more methylol groups per triazine core as a main component, and states that "the composition is useful in the production of process release paper having excellent release properties, gloss, surface condition, and reusability at high temperatures, and can be cured and dried at low temperatures". However, the release agent composition described in Patent Document 1 has insufficient reusability, and there is a problem that the reusability of the process release paper is poor.
[0007] Patent Document 2 discloses a stripper composition comprising an alkyd resin, an amino resin, a silicone resin having a functional group reactive with the alkyd resin and / or the amino resin, and a cationic surfactant, and states that the composition has "excellent gloss, stripping properties, and surface condition, antistatic properties, and excellent reusability." However, the stripper composition of Patent Document 2 has a large change in stripping properties when repeatedly used due to the addition of a surfactant, and improvement in reusability is required.
[0008] Patent Document 3 discloses a process paper for synthetic leather production, which is composed of a cured product of a stripper composition containing a melamine resin and a silicone-modified alkyd resin, wherein the content of the silicone-modified alkyd resin is a specific amount relative to the melamine resin. It is described as "having high gloss, excellent scratch resistance, and high repeatability." However, the stripper composition of Patent Document 3 needs to improve its stripping properties, and has the disadvantage that the surface state of the coating film of the stripper is easily deteriorated.
[0009] Patent Document 4 discloses a stripper composition comprising a resin selected from acrylic resins and alkyd resins; a resin selected from fully ether type methylated melamine resins, methylol type methylated melamine resins and polymers thereof; a silicone resin; and a monohydric alcohol having 1 to 8 carbon atoms, and states that "the stripping property and repeated use property are good, the curing property at low temperature is excellent, and the storage stability is excellent". However, the stripper composition of Patent Document 4 also needs to improve the stripping property, and has a disadvantage that the surface state of the coating film of the stripper is easily deteriorated.
[0010] Prior art literature
[0011] Patent Literature
[0012] Patent Document 1: Japanese Patent Application Publication No. 2000-095929
[0013] Patent Document 2: Japanese Patent No. 4827282
[0014] Patent Document 3: Japanese Patent No. 6707795
[0015] Patent Document 4: International Publication No. 2020 / 153281 Summary of the invention
[0016] Problems to be solved by the invention
[0017] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a release agent composition having good releasability and reusability and having an excellent surface state of a release agent coating film.
[0018] Means for solving problems
[0019] The present inventors have conducted intensive studies to achieve the above-mentioned purpose, and as a result, have found that by preparing a release agent composition comprising (A) an alkyd resin having a hardness of 8 to 30 MPa, (B) an amino resin, and (C) an organopolysiloxane having a functional group that can chemically bond to one or more resins of the components (A) and (B) in a specific mass ratio, a release agent composition having good releasability and reusability, being less likely to cause depressions in the coating film when the release agent is applied to form a coating film, having excellent glossiness of the coating surface, and having excellent surface condition can be obtained.
[0020] Therefore, the present invention provides the following inventions.
[0021] 1. A stripping agent composition comprising:
[0022] (A) Alkyd resin with a hardness of 8 to 30 MPa,
[0023] (B) amino resin, and
[0024] (C) An organopolysiloxane having, in one molecule, two or more functional groups chemically bondable to one or more resins selected from the component (A) and the component (B).
[0025] 2. The release agent composition according to 1, wherein the hydroxyl value of the component (A) is 120 to 150 mgKOH / g.
[0026] 3. The release agent composition according to 1 or 2, wherein a mass ratio (A) / (B) of the component (A) to the component (B) is 66 / 34 to 38 / 62.
[0027] 4. The release agent composition according to any one of 1 to 3, wherein a mass ratio (C) / (B) of the component (C) to the component (B) is 1 / 99 to 20 / 80.
[0028] 5. A release paper or a release film, which is a hard release paper or a release film having a substrate and a release layer formed on the surface thereof, wherein the release layer is composed of a cured product of the release agent composition according to any one of 1 to 4.
[0029] Effects of the Invention
[0030] The release agent composition of the present invention has good releasability and reusability, and when a release layer is formed, a release agent composition having an excellent surface state of the release layer can be provided. DETAILED DESCRIPTION
[0031] Hereinafter, the present invention will be described in more detail.
[0032] [(A)Component]
[0033] The component (A) of the present invention is an alkyd resin having a hardness of 8 to 30 MPa, and one or more thereof can be used alone or in combination. The alkyd resin is a synthetic resin obtained by polycondensation and transesterification of polyols and polyacids with fatty acids or fatty oils. The alkyd resin can be synthesized, for example, according to a conventionally known method described in Japanese Patent Application Publication No. 2007-308658, and a commercially available product can be used.
[0034] Specific examples of polyols in the monomers forming the alkyd resin include, for example, diols such as ethylene glycol, polyethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, polypropylene glycol, 1,3-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2,2-dialkyl-1,3-propanediol, 2,4,4-trimethyl-1,3-pentanediol, butanediol, hydrogenated bisphenol A, ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, and trivalent or higher polyols such as glycerol, trimethylolethane, trimethylolpropane, pentaerythritol, and tris-(2-hydroxyethyl)isocyanurate. These polyols can be used alone or in appropriate combinations of two or more. Among them, it is preferred to use a dihydric alcohol as an essential polyol component and to use a trihydric or higher polyol in combination as necessary.
[0035] Among the monomers forming the alkyd resin, specific examples of polybasic acids include phthalic anhydride, terephthalic acid, succinic acid, adipic acid, sebacic acid and other saturated polybasic acids; unsaturated polybasic acids such as maleic acid, maleic anhydride, fumaric acid, itaconic acid, citraconic anhydride, isophthalic acid and trimellitic anhydride; polybasic acids based on Diels-Alder reaction such as cyclopentadiene-maleic anhydride adducts, terpene-maleic anhydride adducts and rosin-maleic anhydride adducts, etc. It should be noted that in addition to the above-mentioned polybasic acids, benzoic acid as a monobasic acid may also be used in combination.
[0036] Specific examples of fatty acids or fatty oils include caprylic acid, lauric acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, eleostearic acid, ricinoleic acid and dehydrated ricinoleic acid, linseed oil, soybean oil, safflower oil, Chinese tung oil, hempseed oil, perilla oil, tall oil, rice bran oil, castor oil, dehydrated castor oil, rapeseed oil, cottonseed oil, coconut oil, fish oil, cod liver oil and other animal and plant oils, and fatty acids thereof, and preferably coconut oil, soybean oil, castor oil and dehydrated castor oil are used.
[0037] As for the alkyd resin, known alkyd resins can be used. For example, products made from animal and vegetable oils or animal and vegetable oil fatty acids, various saturated fatty acids, etc. can be used. The oil content of these alkyd resins is preferably 0 to 65, more preferably 25 to 55, further preferably 27 to 45, and particularly preferably 29 to 40. Among them, coconut oil-modified alkyd resins, soybean oil-modified alkyd resins, and castor oil-modified alkyd resins are preferably used, and coconut oil-modified alkyd resins are particularly preferred. It should be noted that, within the scope of not impairing the effects of the present invention, acrylic resins, polyester resins, epoxy resins, phenolic resins, etc. can also be modified or mixed in these alkyd resins for use.
[0038] The hardness of the alkyd resin is 8 to 30 MPa, preferably 9 to 25 MPa, and more preferably 10 to 20 MPa. If the hardness is less than 8 MPa, depressions are easily generated on the coating surface, and the surface condition deteriorates. On the other hand, if the hardness is greater than 30 MPa, the synthesis of the alkyd resin becomes difficult.
[0039] It should be noted that the hardness referred to in this specification is a value measured by a nanoindentation method, for example, a nanoindenter (Triboindenter TI-950 manufactured by Hysitron Inc.) is used, at room temperature 23°C, and a Berkovich-type indenter is pressed into an alkyd resin at a maximum penetration depth of 100 nm, and the measurement data is analyzed using a dedicated software (triboscan) attached to the measuring device.
[0040] The weight average molecular weight of the alkyd resin is preferably 40000 to 300000, more preferably 60000 to 280000, further preferably 80000 to 260000, particularly preferably 100000 to 240000. When the weight average molecular weight is within the above range, the surface state is more favorable.
[0041] In addition, the weight average molecular weight mentioned in this specification is a value obtained by gel permeation chromatography (GPC) under the following conditions, using polystyrene as a standard substance.
[0042] [Measurement conditions]
[0043] GPC: HLC-8320 (manufactured by Tosoh Corporation)
[0044] Developing solvent: tetrahydrofuran (THF)
[0045] Flow rate: 0.6mL / min
[0046] Detector: Differential Refractive Index Detector (RI)
[0047] Column: TSK Guardcolomn SuperH-L
[0048] TSKgel SuperHM-N(6.0mmI.D.×15cm×1)
[0049] TSKgel SuperH2500(6.0mmI.D.×15cm×1)
[0050] (All manufactured by Tosoh Corporation)
[0051] Column temperature: 40°C
[0052] Sample injection volume: 50 μL (0.5 wt% THF solution)
[0053] The hydroxyl value of the alkyd resin is preferably 100 to 165 mgKOH / g, more preferably 120 to 150 mgKOH / g. If the hydroxyl value is within the above range, the peelability and repeated use properties are better. It should be noted that the value of the hydroxyl value is a value measured by the potentiometric titration method specified in JIS K0070:1922.
[0054] [(B) ingredient]
[0055] The amino resin used in the present invention is a resin obtained by a condensation reaction of a compound having an amino group and an aldehyde, and serves as a crosslinking agent that reacts with component (A) and / or component (C), and one or more kinds of amino resins can be used. For example, amino resins can be synthesized according to a known method described in Japanese Patent Application Laid-Open No. 53-061684, and commercially available products can be used.
[0056] Examples of the amino resin include urea S resin, melamine resin, aniline resin, and guanamine resin. From the viewpoint of curability, melamine resin is preferred.
[0057] Melamine resin is a synthetic resin obtained by condensing melamine and formaldehyde, and is a condensate composed of a monomer or a polymer of dimer or more. It contains a structure in which a functional group is bonded to the periphery of a triazine ring via three nitrogen atoms, and as a functional group, it has an imino group, a hydroxymethyl group, or an alkoxymethyl group in one molecule, and according to the functional group, it can be listed as a full ether type, a hydroxymethyl type, an imino type, and a hydroxymethyl / imino type.
[0058] Melamine resins are classified according to the types of alkoxymethyl groups, and examples thereof include methylated melamine resins in which all alkoxymethyl groups are methoxymethyl groups, n-butylated melamine resins in which all alkoxymethyl groups are n-butoxymethyl groups, and methylated / n-butylated melamine resins in which methoxymethyl groups and n-butoxymethyl groups are mixed in the alkoxymethyl groups.
[0059] As for the melamine resin, from the viewpoint of releasability, a fully ether type methylated melamine resin, a fully ether type methylated / n-butylated melamine resin, a methylol type methylated melamine resin, and a methylol type methylated / n-butylated melamine resin are preferred, a fully ether type methylated melamine resin and a methylol type methylated melamine resin are more preferred, and a fully ether type methylated melamine resin is further preferred.
[0060] Commercially available melamine resins include, for example, Semmel 300, Semmel 301, and Semmel 303LF (the above are Semester Co., Ltd., fully ether type methylated Melamine resin), Semmel 350, Semmel 370N (the above are hydroxymethyl-type methylated melamine resins manufactured by Semester Co., Ltd.), Semester 325, Semesterル327 (the above is an imino-type methylated melamine manufactured by オルネクスジャパン Co., Ltd. Resin), サイメル232, サイメル235 (the above are オルネクスジャパン Co., Ltd. Co., Ltd., fully ether-type methylated / n-butylated melamine resin), Semmel 251 (the above is Sedum Co., Ltd., hydroxymethyl-type methylated / n-butylated melamine resin), etc.
[0061] The mass ratio (A) / (B) of the component (A) to the component (B) is preferably 66 / 34 to 38 / 62, more preferably 62 / 38 to 40 / 60, further preferably 58 / 42 to 43 / 57, and particularly preferably 55 / 45 to 46 / 54. If the mass ratio (A) / (B) of the component (A) to the component (B) is within the above range, the repeated use property and the surface state are better. The proportion of the component (B) in the total of the components (A) to (C) is not particularly limited, and may be 10 to 90% by mass, preferably 20 to 80% by mass, and more preferably 35 to 60% by mass.
[0062] [(C) ingredient]
[0063] The (C) component of the present invention is an organopolysiloxane having two or more functional groups in one molecule that can be chemically bonded to one or more resins selected from the (A) component and the (B) component, and can be used alone or in combination of two or more appropriately. The organopolysiloxane needs to have two or more functional groups in one molecule that can be chemically bonded to one or more resins selected from the (A) component and the (B) component. Thus, by obtaining a structure in which the (A) component and the (B) component that form the peeling layer are chemically bonded to the organosilicone resin as a demoulding component in the peeling layer, the migration of the organosilicone resin to the pressure-sensitive adhesive layer can be suppressed. As such a functional group, hydroxyl, amino, carboxyl, epoxy, isocyanate, silanol, aminosilyl, etc. can be listed, preferably amino, hydroxyl, epoxy, more preferably hydroxyl.
[0064] The organopolysiloxane may have any structure, such as a linear or branched structure, within the range in which the effects of the present invention can be exhibited, and is preferably represented by the following average composition formula (1).
[0065] [Chemistry 1]
[0066]
[0067] (Where R 1 They may be the same or different, and are unsubstituted or substituted organic groups with 1 to 20 carbon atoms, and have two or more organic groups with 1 to 20 carbon atoms that may be replaced by heteroatoms and have hydroxyl, amino, carboxyl, epoxy or isocyanate groups in one molecule. a is 2 or more, b is 1 or more, c is 0 or more, and d is an integer of 0 or more, and 5≤a+b+c+d≤500.)
[0068] Preferred examples of the organic group having 1 to 20 carbon atoms include, specifically, alkyl groups having 1 to 6 carbon atoms such as methyl, ethyl, propyl, and butyl, cycloalkyl groups having 5 to 8 carbon atoms such as cyclohexyl, aryl groups having 6 to 10 carbon atoms such as phenyl and tolyl, and aralkyl groups having 7 to 10 carbon atoms such as benzyl. Alternatively, alkyl groups having 1 to 10 carbon atoms selected from hydroxypropyl, 1-chloropropyl, 3,3,3-trifluoropropyl, etc., in which a part or all of the hydrogen atoms bonded to the carbon atoms of these groups are substituted with polyether groups, alkoxyalkyl groups, halogen atoms, etc., can be mentioned. Among them, methyl and phenyl are more preferred from the viewpoint of peelability.
[0069] Examples of the organic group having 1 to 20 carbon atoms and which may be substituted by a hetero atom and which has a hydroxyl group, an amino group, a carboxyl group, an epoxy group or an isocyanate group include hydroxyalkyl groups such as hydroxymethyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, hydroxypentyl, hydroxyhexyl, hydroxyheptyl and hydroxyoctyl, and groups such as -(CH2)3-(OCH2CH2) n -OH represented by polyethylene glycol group, -(CH2)3-(OCH2CH2CH2) n -OH represented by a polypropylene glycol group, a 3-aminopropyl group, an N-2-(aminoethyl)-3-aminopropyl group, a carboxy octyl group, a 3-glycidyloxypropyl group, a 2-(3,4-epoxycyclohexyl)ethyl group, and a 3-isocyanate propyl group. Among them, from the viewpoint of curability, a hydroxyalkyl group, a polyethylene glycol group, and a polypropylene glycol group are more preferred.
[0070] The functional group R 1 The content of aryl groups and aralkyl groups is preferably 5 to 50 mol%, more preferably 8 to 45 mol%, further preferably 11 to 40 mol%, and particularly preferably 14 to 35 mol%. Within the above range, the peeling property is more favorable.
[0071] Regarding a, b, c, and d in the above formula (1), a is an integer greater than 2, preferably an integer from 2 to 30, b is an integer greater than 1, preferably an integer from 1 to 500, c is an integer greater than 0, preferably an integer from 0 to 10, d is an integer greater than 0, preferably an integer from 0 to 10, and 5≤a+b+c+d≤500, preferably 10≤a+b+c+d≤400, and more preferably 20≤a+b+c+d≤300.
[0072] Specific examples of the component (C) include the following, but are not limited to these. In the following formula, Me and Ph represent a methyl group and a phenyl group, respectively, and the bonding order of each siloxane unit is not limited to the following order.
[0073] [Chemistry 2]
[0074]
[0075] The mass ratio (C) / (B) of the component (C) to the component (B) is preferably 1 / 99 to 20 / 80, more preferably 1.5 / 98.5 to 16 / 84, further preferably 2 / 98 to 12 / 88, and particularly preferably 2.5 / 97.5 to 10 / 90. When the mass ratio (C) / (B) of the component (C) to the component (B) is within the above range, the peeling property is further improved.
[0076] [(D) ingredient]
[0077] In the composition of the present invention, as the component (D), any amount of solvents may be used alone or in combination of two or more. By diluting with a solvent, handling properties and coating workability are improved.
[0078] Usable solvents include aromatic hydrocarbon compounds such as toluene and xylene, aliphatic hydrocarbon compounds such as hexane, heptane and isoparaffin, ketone compounds such as acetone, methyl ethyl ketone and methyl isobutyl ketone, ester compounds such as ethyl acetate and butyl acetate, ether compounds such as diisopropyl ether and 1,4-dioxane, and alcohol compounds such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol and 2-butanol. Aromatic hydrocarbon compounds, ketone compounds, ester compounds and alcohol compounds are preferred, and toluene, xylene, acetone, methyl ethyl ketone, ethyl acetate, butyl acetate, methanol and 1-butanol are particularly preferred. Any compound that can dissolve the solvent may be used.
[0079] The amount of the component (D) when added is preferably 20 to 10,000 parts by mass, more preferably 50 to 5,000 parts by mass, based on 100 parts by mass of the total of the components (A) to (C).
[0080] [(E) ingredient]
[0081] In the composition of the present invention, from the perspective of promoting the crosslinking reaction of component (A), component (B) and component (C), an acidic catalyst can be used. With regard to the acidic catalyst, one can be used alone or two or more can be used in combination. As the acidic catalyst, for example, inorganic acids such as hydrochloric acid, sulfuric acid, phosphoric acid, boric acid, organic acids selected from organic sulfonic acids such as carboxylic acids such as acetic acid, monochloroacetic acid, dichloroacetic acid, butyric acid, benzenesulfonic acid, p-toluenesulfonic acid, xylenesulfonic acid, p-phenolsulfonic acid, methanesulfonic acid, ethanesulfonic acid, dodecylbenzenesulfonic acid, etc. can be listed, preferably the use of organic acids, more preferably p-toluenesulfonic acid, dodecylbenzenesulfonic acid.
[0082] The amount of the acidic catalyst used in the composition is the amount of catalyst that promotes the reaction, for example, preferably 0.1 to 20 parts by mass, more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the total of components (A) to (C). Within the above range, the curing property is excellent, and the stripping property and reusability are good. When components (D) to (E) are used, the total amount of components (A) to (E) in the stripper composition of the present invention is appropriately selected within the range of 80 to 100% by mass.
[0083] [Other optional ingredients]
[0084] As far as the stripper composition of the present invention is concerned, optional components other than the above components can be further added within the scope that does not impair the effect of the present invention. As optional components, for example, antioxidants such as phenolic, quinone, amine, phosphorus, phosphite, sulfur, and thioether can be used; light stabilizers such as triazole and benzophenone; flame retardants such as phosphate, halogen, phosphorus, and antimony; dyes; pigments; defoamers; fillers; leveling agents; tackifiers; surfactants, etc. These optional components can be used alone or in combination of two or more. It should be noted that in the stripper composition of the present invention, from the perspective of repeated durability, the amount of cationic surfactant is preferably small, or it may not be combined. As for the amount of optional components, as long as it is within the scope that does not impair the effect of the present invention, it is not particularly limited, and preferably 20% by mass or less in the stripper composition.
[0085] [Manufacturing method]
[0086] The composition of the present invention can be prepared by mixing components (A) to (C), components (D) and (E) as needed, and optional components. From the perspective of storage stability, the following method is preferred: (A), (B), (C), (D) and optional components are uniformly mixed in advance, and then component (E) is added immediately before use. There is no particular limitation on the mixing method, and a known method can be used.
[0087] [Release paper or release film (coating)]
[0088] The present invention provides a release paper or a release film, which is a hard release paper or a release film having a substrate and a release layer formed on the surface thereof, wherein the release layer is composed of a cured product of the release agent composition. The release paper or the release film can be obtained by applying the release agent composition to a substrate and then heating it to form a cured film.
[0089] Specifically, for example, the release agent composition is directly applied or further diluted with the dilution solvent in the above range, and then applied to one or both sides of a sheet-like substrate such as paper or film at a rate of 0.01 to 100 g / m2 by a coating method such as coating with a comma coater, lip coater, roll coater, die coater, knife coater, blade coater, bar coater, lick coater, gravure coater, wire rod coater, etc., screen coating, dip coating, cast coating, etc. 2 Thereafter, the substrate is heated at 50 to 200° C. for 1 to 120 seconds to form a cured film on the substrate, thereby forming a release layer.
[0090] The coating amount is preferably 0.01 to 100 g / m 2 , more preferably 0.03 to 20 g / m 2 The drying temperature is preferably 50 to 200° C., more preferably 70 to 180° C. The drying time is preferably 1 to 120 seconds, more preferably 5 to 90 seconds. When the release layer is formed on both sides of the substrate, it is preferred to perform the formation operation of the cured film (release layer) on one side of each substrate.
[0091] Examples of sheet-like substrates include polyethylene laminated paper, glassine paper, fine paper, kraft paper, clay-coated paper, various coated papers such as mirror coated paper, synthetic papers such as Yupo, polyethylene films, polypropylene films such as CPP and OPP, polyester films such as polyethylene terephthalate films, polyamide films, polyimide films, polylactic acid films, polyphenolic films, polycarbonate films, etc. In order to improve the adhesion of these substrates to the release layer, products in which the substrate surface has been subjected to corona treatment, etching treatment or plasma treatment can be used.
[0092] Example
[0093] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0094] <Raw materials used>
[0095] (A ingredient)
[0096] (A-1) Coconut oil-modified alkyd resin (50% by mass xylene solution, hydroxyl value 133 mgKOH / g) 10.9
[0097] (A-2) Coconut oil-modified alkyd resin (50% by mass xylene solution, hydroxyl value 139 mgKOH / g) 12.5
[0098] (A-3) Coconut oil-modified alkyd resin (50% by mass xylene solution, hydroxyl value 125 mgKOH / g) 16.4
[0099] (A-4) Coconut oil-modified alkyd resin (50% by mass xylene solution, hydroxyl value 142 mgKOH / g) 8.6
[0100] (A-5) Comparative product, Harifter 732-60 (manufactured by Harima Chemicals, 60% by mass xylene solution of coconut oil-modified alkyd resin, hydroxyl value 130 mgKOH / g) 4.1
[0101] (A-6) Comparative product, Alcidia J-524-A (manufactured by DIC, 60% by mass xylene solution of coconut oil-modified alkyd resin, hydroxyl value 126 mgKOH / g) 6.8
[0102] (Component B)
[0103] (B-1)
[0104] SAMULA 303LF (manufactured by SAMULA: full ether type methylated melamine resin)
[0105] (Component C)
[0106] (C-1)
[0107] Polyorganosiloxane represented by the general formula (3): Me and Ph in the following formula represent a methyl group and a phenyl group, respectively, and the bonding sequence of each siloxane unit is not limited to the sequence shown below.
[0108] [Chemistry 3]
[0109]
[0110] (C-2)
[0111] Polyorganosiloxane represented by the general formula (4): Me and Ph in the following formula represent a methyl group and a phenyl group, respectively, and the bonding sequence of each siloxane unit is not limited to the sequence shown below.
[0112] [Chemistry 4]
[0113]
[0114] (Component D)
[0115] Mixed solution of toluene and xylene (mass ratio 50:50)
[0116] (Ingredient E)
[0117] p-Toluenesulfonic acid
[0118] [hardness]
[0119] The hardness of component (A) was measured by nanoindentation using a nanoindenter (Triboindenter TI-950 manufactured by Hysitron Inc.). Component (A) was weighed in a circular aluminum dish having a diameter of 6 cm and a depth of 1 cm so that the solid content of component (A) was 10 g, and heated in a hot air dryer at 150° C. for 5 hours to volatilize the solvent. Then, the mixture was naturally cooled for 24 hours at room temperature of 23° C. to obtain a measurement sample.
[0120] The obtained sample was fixed on a dedicated sample fixing table so that the surface of component (A) was in contact with the indenter, and the data obtained when the Berkovich type indenter was pressed into the surface of component (A) at a speed of about 17 nm / sec and a depth of about 100 nm at room temperature 23°C was analyzed using dedicated software (triboscan) to obtain the hardness. The same operation was performed on 5 different points in each sample to obtain the hardness, and the average value is recorded in Tables 1 and 2.
[0121] [Examples 1 to 6, Comparative Examples 1 to 4]
[0122] Using the components (A) to (C) shown above as raw materials, the coating composition is prepared by the following steps. Components (A), (B), and (C) are taken into a flask according to the mixing ratios in Tables 1 and 2, and component (D) is added in a manner that the solid content concentration becomes 40% by mass, and mixed evenly. To the obtained solution, component (E) is added so that it becomes 5 parts by mass relative to a total of 100 parts by mass of components (A) to (C), and stirred and mixed to obtain a release agent composition. Using this composition, a release paper having a release layer is prepared by the method described below, and the following evaluation is performed. The results are recorded in the table.
[0123] Although the component (A) contains a solvent, the blending amounts in the tables do not include the pure amount of the solvent.
[0124] [Peel strength]
[0125] The obtained release agent composition was applied to a mirror coated paper having a thickness of 165 μm by a bar coater so that the coating amount became 5.0 g / m 2, heated in a hot air dryer at 170°C for 60 seconds to form a release agent layer, a single-liquid polyurethane solution [Chrisbond 5516S (manufactured by Dainippon Ink and Chemicals Co., Ltd.)] was applied to the surface of the cured film so that the thickness of the coating became 30 μm, and heat-treated at 130°C for 2 minutes to form a polyurethane layer. Secondly, a Nitto 31B tape was attached to the treated surface, and a 2Kg roller was used to reciprocate and press once. After aging at 25°C for 20 hours, the sample was cut into 3 cm wide, and a tensile tester was used to stretch the attached tape at an angle of 180° and a peeling speed of 0.3 m / min to measure the force required for peeling (gf / 30 mm). This value was used as the first peel strength and evaluated based on the following indicators.
[0126] ○: The first peel strength is 20gf / 30mm or less
[0127] △: The first peel strength is greater than 20gf / 30mm and less than 30gf / 30mm
[0128] ×: The first peel strength is greater than 30 gf / 30 mm
[0129] [Reusability]
[0130] In the same manner as in the above-mentioned peel strength test, after forming the release agent layer, a polyurethane solution was applied to form a polyurethane layer. The polyurethane peeling was repeated three times, and the third measured value was defined as the third peel strength.
[0131] The increase rate of the peeling force during repeated use was calculated from the formula (3rd peeling strength - 1st peeling strength) / 1st peeling strength × 100 (%). The smaller the increase rate, the better the repeated use property. Evaluation was performed based on the following indexes.
[0132] ○: Increase rate is less than 20%
[0133] △: Increase rate is more than 20% and less than 50%
[0134] ×: Increase rate exceeds 50%
[0135] [Surface condition (depression)]
[0136] The coating film surface (400 cm 2 The fewer the number of depressions, the better the surface condition, and the evaluation was performed based on the following indices.
[0137] ○: The number of depressions is 0 to 2
[0138] △: The number of depressions is 3 to 5
[0139] ×: The number of depressions is 6 or more
[0140] [Surface condition (gloss)]
[0141] The specular gloss at 60 degrees of the coating film surface formed in the peel strength test was measured using a gloss meter VG7000 manufactured by Nippon Denshoku Industries Co., Ltd. The higher the specular gloss, the better the surface condition, and the evaluation was performed based on the following indexes.
[0142] ○: Mirror glossiness is 96% or more
[0143] △: Specular glossiness is 92% or more and less than 96%
[0144] ×: Specular glossiness is less than 92%
[0145] [Table 1]
[0146]
[0147] [Table 2]
[0148]
Claims
1. A stripping agent composition comprising: (A) Alkyd resin with a hardness of 8 to 30 MPa, (B) amino resin, and (C) An organopolysiloxane having, in one molecule, two or more functional groups chemically bondable to one or more resins selected from the component (A) and the component (B).
2. The stripping agent composition according to claim 1, wherein The hydroxyl value of the component (A) is 120 to 150 mgKOH / g.
3. The stripping agent composition according to claim 1, wherein The mass ratio (A) / (B) of the component (A) to the component (B) is 66 / 34 to 38 / 62.
4. The stripping agent composition according to claim 1, wherein The mass ratio (C) / (B) of the component (C) to the component (B) is 1 / 99 to 20 / 80.
5. A release paper or a release film, which is a hard release paper or a release film comprising a substrate and a release layer formed on the surface thereof, wherein the release layer is composed of a cured product of the release agent composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
JP1973027282A
Preparation of methylletherified methylol melamine resin
JP1978061684A
Release agent composition for process release paper
JP2000095929A
Production method for transesterification product and production method for alkyd resin using the transesterification product
JP2007308658A
Resin composition for release paper or release film, and release paper or release film
WO2020153281A1